PENERAPAN MODEL PJBL BERBASIS CRT UNTUK MENINGKATKAN KREATIVITAS MATA PELAJARAN SENI RUPA KELAS V SD PLUS IGM PALEMBANG - Alfiani Masruroh; Yenny Anwar; Atika Dwi Martanti (Yayasan Nusantara Hasana Berdikari, 2025)
Fine art is one of the subjects that plays an important role in the development of creativity, imagination, and critical thinking skills of students. At the elementary school level, fine arts learning not only aims to hone fine motor skills, but also as a means of self-expression and cultural appreciation. The purpose of the study was to analyze how the application of the Project Based Learning (PjBL) model based on Culturally Responsive Teaching (CRT) in fine arts learning can improve students' creativity in fine arts subjects. This type of research uses classroom action research (PTK). The research procedure consists of four stages, namely planning, action, observation, and reflection. Data collection techniques using observation and portopolio analysis. Data analysis with P = F: n x 100%. Based on classroom action research in class V SD Plus Indo Global Mandiri (IGM) Palembang in two cycles, the application of the Project Based Learning (PjBL) learning model with a Culturally Responsive Teaching (CRT) approach proved effective in increasing student creativity, which was initially 37.70% (sufficient category) in the pre-cycle, increased to 61.46% (good) in cycle I, and reached 86, 88% (excellent) in cycle II, fulfilling all indicators of creativity achievement through the project of making a pencil case from woven jute rope that encourages original ideas, creative thinking skills, and active involvement of students according to their culture and experience, so that CRT-based PjBL is considered capable of creating a meaningful, inclusive, and optimal learning environment for the development of student creativity.